Seroprevalence of bovine brucellosis and associated risk factors in Nakasongola district, Uganda - Bugeza, James; Muwonge, Adrian; Munyeme, Musso; Lasuba, Phillip; Jacques, Godfroid; Kankya, Clovice (Tropical Animal Health and Production, 2019)
A cross-sectional study was carried out between November 2015 and January 2016 to determine the seroprevalence of Brucella antibodies in cattle raised under communal, fenced farms and tethering systems and the associated factors. Seven hundred twentyeight bovine serawere collected and testedwith rose Bengal test as a screening test and the indirect enzyme-linked immunosorbent assay as a confirmatory test. Animal- and herd-level data were collected and binary logistic regression was used to assess the potential risk factors. True animal- and herd-level prevalence was highest in the fenced farms (4.5% (95%CI, 2.3–6.9) and 19.5% (95%CI, 8.2–32.7) respectively). The risks for natural brucellosis infection were sharing water with wild animals (OR = 0.21, 95%CI, 0.104–0.83), herd size (medium: OR = 0.089, 95%CI 0.017–0.449; large: OR = 0.024, 95%CI 0.003–0.203), fenced farms (OR = 3.7, 95% CI, 1.7–7.9), sex (OR = 0.03, 95%CI, 0.01–0.079), and lactation (OR = 0.013, 95%CI, 0.004–0.049). Changes in rangeland tenure and the shift towards intensive cattle production have influenced brucellosis epidemiology. Future studies should aim at identifying the infecting Brucellae and examining the role of wildlife in brucellosis epidemiology.
Keywords: Brucellosis; Production systems; Rangeland tenure; Uganda